António Salazar i jego „Nowe Państwo” – geneza, zręby ideowe, specyfika - Nowak-Vilela, Monika (Acta Universitatis Lodziensis. Folia Historica, 2013)
The subject of the article António Salazar and his "New State" – the genesis, ideological foundations, the specificity is the long-term Prime Minister of Portugal, and de facto its dictator, who formulated the concept of state functioning, which was later defined as the New State (Estado Novo). The text shows the leader of the Portuguese Republic as a man and an ideologist as well as the process of development of his views on the background of landmark events in the Iberian Peninsula in the early twentieth century. The aim was to present all the theoretical assumptions of Estado Novo's ideas rather than its practical implementation after the proclamation of the New State constitution in 1933. That is why the mentioned date closes the article's timing framework. The ideology of António Salazar and the structures he created survived in virtually unchanged form until 1974. Hence, the second important goal of the text is to try to answer the question of Salazar's government's longevity.